Acyl-sulfamates Target the Essential Glycerol-Phosphate Acyltransferase (PlsY) in Gram-Positive Bacteria - Cherian, Philip (2012)
PlsY is the essential first step in membrane phospholipid synthesis of Gram-positive pathogens. PlsY catalyzes the transfer of the fatty acid from acyl-phosphate to the 1-position of glycerol-3-phosphate to form the first intermediate in membrane biogenesis. A series of non-metabolizable, acyl-sulfamate analogs of the acyl-phosphate PlsY substrate were prepared and evaluated as inhibitors of Staphylococcus aureus PlsY and for their Gram-positive antibacterial activities. From this series phenyl (8-phenyloctanoyl) sulfamate had the best overall profile, selectively inhibiting S. aureus phospholipid biosynthesis and causing the accumulation of both long-chain fatty acids and acyl-acyl carrier protein intermediates demonstrating that PlsY was the primary cellular target. Bacillus anthracis was unique in being more potently inhibited by long chain acyl-sulfamates than other bacterial species. However, it is shown that Bacillus anthracis PlsY is not more sensitive to the acyl-sulfamates than S. aureus PlsY. Metabolic profiling showed that B. anthracis growth inhibition by the acyl-sulfamates was not specific for lipid synthesis illustrating that the amphipathic acyl-sulfamates can also have off-target effects in Gram-positive bacteria. Nonetheless, this study further advances PlsY as a druggable target for the development of novel antibacterial therapeutics, through the discovery and validation of the probe compound phenyl (8-phenyloctanoyl) sulfamate as a S. aureus PlsY inhibitor.